INVENTORY RESERVES AS AN ELEMENT OF INVENTORY POLICY. - Nickerson, Clabence B. (The Accounting Review, 1937)
Abstract This article focuses on the inventory reserves as element of inventory policy. Within the last two years a marked revival of interest in the base-stock method of inventory valuation has developed. Recent literature on the subject has stressed its long-run benefits and its significance under present and prospective conditions of rising prices. These aspects are of major importance, though doubtless the interest of many advocates has been quickened by the possibilities of the method in the computation of profit subject to the undistributed profits tax, should the government allow it for this purpose in the near future. The article describes the important features of the base-stock method and some of the implications and fundamental concepts involved in it. Following this, an alternative procedure now in use, namely the stated reserve method, is presented for consideration in the belief that, as a practical matter at the present time, it is desirable to devote attention to alternatives which involve less drastic changes in traditional practice and yet provide the major advantages of the base-stock method.